NK cell-derived extracellular vesicles enhance cytotoxicity and immune cell recruitment in non-small cell lung cancer - Palade, Joanna; Alsop, Eric; Tang, Nanyun; Antone, Jerry; Paredes, Dorothy M.; Halder, Tithi Ghosh; Soldi, Raffaella; Bargenquast, Taylor; Schwartz, Gary; Finholt, Jennifer; Snipes, George J.; Sharma, Sunil; et al. (Frontiers in Immunology, 2025)
IntroductionImmune-based agents, especially Immune Checkpoint Inhibitors (ICI), are standard of care therapy in non-small cell lung cancers (NSCLC); however, a significant number of patient tumors fail to respond, or develop resistance. While target expression, mutation burden and oncogenic pathways impact responses, an established mechanism contributing to ICI therapy failure is evasion of T-cell responses via downregulation of human leukocyte antigen (HLA). Conversely, natural killer (NK) cells effector function is enhanced in the absence of HLA, making NK cellular therapies an attractive option for ICI resistant tumors. Challenges for current NK cell therapies include failure to adequately infiltrate solid tumors and long-term persistence, which may be overcome by deploying NK-derived extracellular vesicles (NKEVs) as a personalized novel adoptive cellular therapeutic with cytotoxic effects.MethodsIn a human NSCLC cohort (n=10), we used single cell RNAseq and antibody labeling (CITEseq) to examine the immune cell landscape in peripheral immune cells (PBMCs) and tumors. NKEVs retrieved from patient NK cells were characterized with proteomics and bulk RNAseq, and EV functionality was assessed using primary tumor organoids.ResultsWe identified circulating NK cell subsets, describing differences in cell composition, gene expression and signaling, related to time point, NSCLC subtype (adenocarcinoma, squamous cell), composition and tumor grade. Next, we examined the functional capabilities of patient NKEVs in organoid structures derived from primary tumor cells, finding that exposure to patient NKEVs resulted in a 40-45% decrease in organoid viability, and significantly lowered the cisplatin dose required to elicit cytotoxicity. In Nivolumab treated PBMC co-culture experiments, NKEV addition favorably shifted the organoid infiltrating immune population to significantly fewer CD4+ T cells and more CD56+ NK cells. Finally, we used the multi-omic characterization of NKEV molecular cargo to identify RNA transcripts and proteins associated with cytotoxic and immune recruiting functions.ConclusionsThis work demonstrated that NKEVs can be successfully harvested from patient derived, expanded NK cells, and highlights their heterogeneous cargo, and anti-tumor properties in combination with standard-of-care therapies.